2021
DOI: 10.1007/s41105-021-00337-6
|View full text |Cite
|
Sign up to set email alerts
|

Sleep disturbance among frontline nurses during the COVID-19 pandemic

Abstract: The main objective of this study is to assess the prevalence of sleep disturbance and related psychological factors (stress, anxiety and depression) among frontline nurses in Oman during the COVID-19 pandemic. A cross-sectional and descriptive correlational design using Qualtrics® software was used in this research. Data were collected using the Pittsburgh Sleep Quality Index (PSQI), the Hospital Anxiety and Depression Scale (HADS) and the Perceived Stress Scale (PSS). Logistic regression was performed to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
1
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 38 publications
1
18
1
2
Order By: Relevance
“…The median number of participants was 338. Excluding manuscripts that reported age as range or median (i.e., 28%) [ 41 , [44] , [45] , [46] , 48 , 59 , [61] , [62] , [63] , 69 , 73 , 75 ], [ 84 , 87 , 96 , [98] , [101] , 104 , 111 , 112 , 121 ], [ 126 , 134 , 137 , 141 , 144 , 145 , 147 ], [ 158 , 161 , [163] , [164] , [165] , 167 , 169 , 175 ], the mean age of the participants was 32.22 ± 9.35 years. Regarding the administered sleep measures, 103 studies reported PSQI scores.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The median number of participants was 338. Excluding manuscripts that reported age as range or median (i.e., 28%) [ 41 , [44] , [45] , [46] , 48 , 59 , [61] , [62] , [63] , 69 , 73 , 75 ], [ 84 , 87 , 96 , [98] , [101] , 104 , 111 , 112 , 121 ], [ 126 , 134 , 137 , 141 , 144 , 145 , 147 ], [ 158 , 161 , [163] , [164] , [165] , 167 , 169 , 175 ], the mean age of the participants was 32.22 ± 9.35 years. Regarding the administered sleep measures, 103 studies reported PSQI scores.…”
Section: Resultsmentioning
confidence: 99%
“… Author Country Sample (n) Female Age Type of pop. Measure NOS Abbas et al, 2021 [ 37 ] Kuwait 217 0.44 x̄ = 35.8y health w. PSQI gen-sub 5 Abid et al, 2021 (a) [ 38 ] Tunisia 48 1 x̄ = 8.66y children PSQI gen 5 Abid et al, 2021 (b) [ 38 ] Tunisia 52 0 x̄ = 8.66y children PSQI gen 5 Akıncı and Başar, 2021 [ 39 ] Turkey 152 0.63 x̄ = 35.8y health w. PSQI gen-sub 5 Akkuş et al, 2021 [ 40 ] Turkey 595 0.66 x̄ = 27.9y general PSQI gen 6 Al Maqbali, 2021 [ 41 ] Oman 987 0.91 >18y health w. PSQI sub 5 Al-Musharaf et al, 2021 [ 42 ] Saudi Arabia 297 1 x̄ = 20.7y general PSQI gen 5 Alfonsi et al, 2021 (a) [ 43 ] Italy 72 1 x̄ = 35.68y general PSQI gen-sub 6 Alfonsi et al, 2021 (b) [ 43 ] Italy <...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they have to deal with severe disease progression among patients and are at risk to get infected themselves [8,9]. These continuous strains are associated with the deterioration of the nurses' mental health: symptoms of depression, anxiety, and inadequate sleeping hours were reported [10] as well as post-traumatic stress disorder (PTSD) among frontline nurses, who have direct contact with COVID-19 patients [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Regular sleep could be an usual issue during practice. Some of nurses may well be working long days and have some difficult in several situations (Al Maqbali, 2021). Therefore, it is important to get quality sleep when having a time during the day.…”
mentioning
confidence: 99%